2018
DOI: 10.1007/s00592-018-1133-z
|View full text |Cite
|
Sign up to set email alerts
|

Defining the contribution of chronic kidney disease to all-cause mortality in patients with type 2 diabetes: the Renal Insufficiency And Cardiovascular Events (RIACE) Italian Multicenter Study

Abstract: CKD is a major contributor to excess mortality in type 2 diabetes, conferring a very high risk in younger patients and fully accounting for excess risk in the older ones. Higher albuminuria and lower eGFR, even in the normal range, identify individuals with increased mortality risk. Trial registration ClinicalTrials.gov (NCT00715481; https://clinicaltrials.gov/ct2/show/NCT00715481 ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
2
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 32 publications
0
25
2
2
Order By: Relevance
“…This finding might be explained by the high burden of CVD in this population (71.7%) and the persistently high risk of cardiovascular death, accounting for 63-69% of all deaths across baseline GFR categories G2-G5. Indeed, a prior study of the contributions of CVD and CKD to all-cause mortality in patients with T2D found that CVD had the strongest association with risk of allcause mortality in patients with and without CKD [23]. However, results in the present study demonstrate that prior CVD and prior CKD were similarly associated with risk of all-cause mortality and, if anything, prior CKD had the strongest association.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This finding might be explained by the high burden of CVD in this population (71.7%) and the persistently high risk of cardiovascular death, accounting for 63-69% of all deaths across baseline GFR categories G2-G5. Indeed, a prior study of the contributions of CVD and CKD to all-cause mortality in patients with T2D found that CVD had the strongest association with risk of allcause mortality in patients with and without CKD [23]. However, results in the present study demonstrate that prior CVD and prior CKD were similarly associated with risk of all-cause mortality and, if anything, prior CKD had the strongest association.…”
Section: Discussioncontrasting
confidence: 79%
“…If any aspect of the observed association between baseline GFR and risk of all-cause mortality (as reported in the present and previous studies [17,18,20,21,23,36]) are causally connected (in other words, not an epiphenomenon), efforts to identify and limit the progression of CKD need to be pushed to the forefront of clinical care. The treatment of patients with T2D and at high risk of developing CVD or CKD is complex.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…CKD is highly prevalent in T2D and is a strong accelerator of cardiovascular risk . In the longitudinal Italian Renal Insufficiency and Cardiovascular Events (RIACE) study, higher AER and lower eGFR, even in the normal range, identified individuals with increased mortality . Other observational studies and meta‐analyses show that an excess cardiovascular morbidity and mortality is linked to impaired renal function .…”
Section: Introductionmentioning
confidence: 99%
“…11 In the longitudinal Italian Renal Insufficiency and Cardiovascular Events (RIACE) study, higher AER and lower eGFR, even in the normal range, identified individuals with increased mortality. 12 Other observational studies and meta-analyses show that an excess cardiovascular morbidity and mortality is linked to impaired renal function. 13,14 Therefore, it has been hypothesized that kidney protection contributes to cardiovascular protection in patients treated with SGLT2i.…”
mentioning
confidence: 99%